Electricity Consumption, Public Agricultural Expenditure and Output in Nigeria: A Time Series Dynamic Approach - Okorie, Uchechukwu E.; Osabuohien, Evans S.; Oaikhenan, Hassan E. (International Journal of Energy Economics and Policy, 2020)
This study interrogates the effects of electricity consumption and government agricultural spending on agricultural output in Nigeria using data that spanning through from 1981 to 2017. The unit root test was conducted with Phillip Perron (PP) at constant and trend while the dynamic model of autoregressive distributed lags (ARDL) was used in ascertaining the existence of cointegration among the variables in the model. The outcome of the study shows that poor electricity supply has significantly retarded the level of agricultural output in Nigeria while public agricultural spending indicates a weak positive lag effect on agricultural sector performance. These outcomes capture the adverse effect of shortage in electric energy supply and poor government allocation on agricultural production of goods and services. We, therefore, advocate for sector-driven energy policies that will foster the growth and development of the agricultural sector through mechanisation of agricultural system. Keywords: Electricity Supply, Government Expenditure, Agricultural Sector. JEL Classifications: E23, E62, H54, L94 DOI: https://doi.org/10.32479/ijeep.8436